JPEG2000 Image Compression and Visualization for Desktop and Mobile Clients - Serra, A.; Dias, L.; Serrão, C.; Dias, J. (Proc AECRIS 2006, Atlantic Europe Conference on Remote Imaging and Spectroscopy, Preston, United Kingdom, 2006)
This paper presents an architecture for JPEG2000 image compression and distribution using a Digital Rights Management (DRM) platform in the context of the PIMHAI project. The proposed architecture, based on a client-server interaction, will allow the users to upload images in PCIDSK database (PIX) format using a web-application front-end, and to perform the lossless JPEG2000 compression of such images. The resulting JPEG2000 images are then protected using cryptographic techniques and its intellectual property rights are managed digitally. In the context of the PIMHAI project, the proposed architecture will allow the storage of smaller and cryptographically protected image files in the database. The user access rights enforcement will prevent the access to the images by non authorized users. Another important feature is the decreasing of the connection time in the mobile client, through the expensive and slower wireless channel, to access the images in the database.